A Study On Linguistic Features Of Negative Emotion Expressions In English And Vietnamese Literature - Trần Thị Mỹ Dung (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Emotions are human beings’ specific forms of interaction and environment helping us to cognate the world and define our place in it. Beside positive emotions, negative ones are an unavoidable dimension of human life which are featured in the form of expressions in literary works. Thus, thorough knowledge of expressions denoting negative emotions enables us to realize some specific rules to identify how words are collocated in the journey of perceiving the messages conveyed by writers as well as properly express our emotions to limit unnecessary conflict in communication. The study aims to classify, describe and analyze negative emotion expressions in English and Vietnamese in terms of syntax and semantics based on a survey of 250 samples of negative emotion expressions in English and another 250 in Vietnamese, which are mainly taken from novels, short stories by native writers in both languages. In syntactic aspect, the data were analyzed in view of types of expression, namely nominal expressions, verbal expressions, adjectival expressions and prepositional expressions. In semantic aspect, the data are grouped into four basic emotions that are sadness, anger, fear and disgust. Moreover, negative emotion expressions are also classified into six types of emotions: basic emotions, emotional relations, caused emotions, causative emotions, emotional goals and complex emotions according to Oatley and Johnson-Laird‘s view [1989]. Accordingly, practical and feasible implications are put forward in the language learning and translation in the hope they can benefit not only English learners but also translators and those who are interested in linguistics and literature.